The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s00464-017-5422-3
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic colectomy in obese patients: a comparison of laparoscopic and hand-assisted laparoscopic techniques

Abstract: In comparison to LAP colectomy, the HAL technique is used more often in obese patients with an increased operative risk profile. While inherent bias and unmeasured variables limit the analysis, the available data indicate that the HAL technique is associated with increased perioperative morbidity. Alternatively, HAL and LAP LAR are performed in obese patients with a similar risk profile and result in similar postoperative outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
2
0
2
Order By: Relevance
“…Patients operated by surgical teams with a greater experience in laparoscopic colorectal surgery had a generally shorter duration of postoperative ileus [59] [ 52]. Finally, two studies analyzed surgical technique: Firstly, the study of Overbey et al found that hand-assisted laparoscopic technique was associated with a higher incidence of PPOI compared to laparoscopy alone in obese patients (OR 1.33, 95% CI 1.12-1.57) [60]. Secondly, Aydin et al reported that PPOI was significantly more frequent in patients who underwent Hartmann's reversal compared to those who underwent primary resection and anastomosis (p \ 0.01) [61] Five studies examined analgesia as a potential risk factor for PPOI.…”
Section: Systematic Review Of Risk Factors For Ppoimentioning
confidence: 99%
“…Patients operated by surgical teams with a greater experience in laparoscopic colorectal surgery had a generally shorter duration of postoperative ileus [59] [ 52]. Finally, two studies analyzed surgical technique: Firstly, the study of Overbey et al found that hand-assisted laparoscopic technique was associated with a higher incidence of PPOI compared to laparoscopy alone in obese patients (OR 1.33, 95% CI 1.12-1.57) [60]. Secondly, Aydin et al reported that PPOI was significantly more frequent in patients who underwent Hartmann's reversal compared to those who underwent primary resection and anastomosis (p \ 0.01) [61] Five studies examined analgesia as a potential risk factor for PPOI.…”
Section: Systematic Review Of Risk Factors For Ppoimentioning
confidence: 99%
“…Therefore we strongly comply with the opinion that technical proficiency occurs after approximately 100 cases for HALS [21], which is hardly achievable in rural hospitals and more challenging with LC approach. HALS should be considered not only as bridge procedure, but as best alternative to LC for complicated cases, when difficult rectal dissection (lower or middle part) or colonic mobilization experienced, especially in morbid obese patients with body mass index of 40 or more [6,22,23]. We documented 4 cases of conversion (we defined conversion as lengthening of the incision of that planned at the beginning of procedure) due massive adhesions and one because of bleeding from mesenteric vessels due to non functioning suturing device.…”
Section: Discussionmentioning
confidence: 99%
“…Тем не менее, мы строго придерживаемся мнения о том, что должный опыт хирург получает после примерно 100 операций с использованием HALS [21], что вряд ли возможно в районных больницах и ещё более сложно при использовании стандартного лапароскопического подхода. HALS нужно рассматривать не только как промежуточный этап в освоении лапароскопических технологий, но и как лучшую альтернативу традиционной лапароскопии при сложных случаях, когда возникают трудности при мобилизации среднеи нижне-ампулярного отдела прямой кишки, либо при мобилизации левого изгиба ободочной кишки у тучных пациентов, с индексом массы тела, превышающим 40 [6,22,23]. Нами было задокументировано 4 случая конверсии доступа (конверсией мы называли случаи, когда происходило расширение лапаротомной раны более запланированного) при выраженном спаечном процессе, а также из-за кровотечения из сосудов брыжейки, возникшего из-за поломки сшивающего аппарата.…”
Section: Discussionunclassified
“…Ряд авторов указывает на прогностическую роль таких факторов, как проведение неоадъювантной химиолучевой терапии, высокий уровень перевязки нижней брыжеечной артерии (НБА), пол пациента, наличие обширных спаек в малом тазу, возраст пациента, избыточную массу тела в увеличении риска возникновения послеоперационных осложнений [5,6,7,13,15]. Однако данные целого рядя работ противоречат тем, которые приведены выше [8][9][10].…”
Section: Introductionunclassified